2017
DOI: 10.1051/0004-6361/201731927
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of the decay of the cyclotron line energy in Hercules X-1

Abstract: Recent observations of Her X-1 with NuSTAR and INTEGRAL in 2016 have provided evidence that the 20-year decay of the cyclotron line energy found between 1996 and 2015 has ended and that an inversion with a new increase, possibly similar to the one observed around 1990-1993, has started. We consider this a strong motivation for further observations and for enhanced efforts to significantly improve our theoretical understanding of the accretion process in binary X-ray pulsars. We speculate about the physics behi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…The assumption is that the line energy depends both on time and flux and there is an explicit rise of E cyc with time after T c = 57341. This is equivalent to the model described in Staubert et al (2017). With this model we find the χ 2 /d.o.f to be 22/22, with b 2 =−8.64 +4.05 −4.15 .…”
Section: Of T C (=54487 +515mentioning
confidence: 60%
See 2 more Smart Citations
“…The assumption is that the line energy depends both on time and flux and there is an explicit rise of E cyc with time after T c = 57341. This is equivalent to the model described in Staubert et al (2017). With this model we find the χ 2 /d.o.f to be 22/22, with b 2 =−8.64 +4.05 −4.15 .…”
Section: Of T C (=54487 +515mentioning
confidence: 60%
“…Further observations with INTEGRAL, Suzaku and NuSTAR fit well with a model assuming a continued decay of E cyc until 2015, with a decay rate of 0.260 ± 0.14 keV/yr (Staubert et al 2016). However in 2016 NuSTAR and INTEGRAL observations of Her X-1 began to indicate a possible upward trend in line energy (Staubert et al 2017) (which is not confirmed so far), possi- Xiao et al 2019).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…An intriguing aspect of this issue is the behavior of Her X-1's CRSF energy between 1991 and 1994, when it appears to have jumped by ∼7 keV. Staubert et al (2014) suggested that this indicates that Her X-1's CRSF energy has a natural "floor" of ∼37 keV, and indeed Staubert et al (2017) report evidence that the decay has reversed and the CRSF energy has begun to increase. This is interesting in comparison to the behavior of 4U 1538−522's CRSF, which is certainly consistent with a relatively short-timescale increase.…”
Section: Ingress Eclipse and Egress Spectramentioning
confidence: 99%
“…The CRSF properties of X-ray pulsars are found to be variable for different reasons (Maitra 2017). The CRSF line energy evolves with time in sources like Her X-1 (Staubert et al 2017) and 4U 1538-522 (Hemphill et al 2019). Line energy also shows dependence on X-ray luminosity, for example, in V0332+53 (Doroshenko et al 2017).…”
Section: Introductionmentioning
confidence: 99%